2016
DOI: 10.1097/iop.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of the Myofibroblast in Socket Surgery: An Immunohistochemical Study

Abstract: Purpose:To determine the impact of a single injection of various anti-inflammatory, antimitotic, and antiangiogenic agents on the cell count of myofibroblasts in an eviscerated socket.Methods:One eye from 15 skeletally mature New Zealand white rabbits was eviscerated, and the rabbits were divided into 5 groups. Each group of 3 rabbits received a 0.1 ml subconjunctival injection of a different agent. Group I received bevacizumab 25 mg/ml, group II received triamcinolone 40 mg/ml, group III received 5-fluorourac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Tawfik et al have demonstrated histologically in an animal model that a single injection of mitomycin-C, triamcinolone, 5-Fluorouracil, or bevacizumab could reduce the number of myofibroblasts in an actively healing socket, reducing the tendency to socket contraction. 88 …”
Section: Contracted Socketmentioning
confidence: 99%
“…Tawfik et al have demonstrated histologically in an animal model that a single injection of mitomycin-C, triamcinolone, 5-Fluorouracil, or bevacizumab could reduce the number of myofibroblasts in an actively healing socket, reducing the tendency to socket contraction. 88 …”
Section: Contracted Socketmentioning
confidence: 99%
“…Fibroblasts appear on day 2-3 following injury, while myofibroblasts appear on day 12 when wound contractions are nearly 80% complete [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 is a key mediator that induce α-SMA [11,12]. Alpha-smooth muscle actin (α-SMA) may serve as a reliable marker for myofibroblast cells [12], although others considered it as not a consistent marker for contractile fibroblasts and lots of collagen [13]. Alpha-SMA widely presents in stressed fibers induces cytoskeleton reorganization, increases contractility and stimulates cell migration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations